Uji Coba Penggunaan Teepol Sebagai Bahan Alternatif pada Eksperimen Viskositas di Laboratorium Fisika Dasar - Cahyo Puji Asmoro; Hana Susanti (Universitas Nurul Huda, 2025)
Viscosity experiment is one of the materials given in the Basic Physics experiment course at FPMIPA UPI which aims to measure the viscosity level of a liquid using the Stokes law method or the ball viscosimetry method. Previously, oil was often used as a test material, but its thick color made observation of the ball in the liquid difficult, especially when using software such as trackers that require visual clarity. The purpose of this study was to examine the alternative of using teepol as a test material. The research method applied is the experimental method of replacing oil with teepol. From the results of experimental data collection using Stokes' law, with 4 balls of different diameters, the viscosity value of teepol ranges from 3.36 to 4.55 kg/ms. The consistent, reliable and valid measurement results show that teepol is reliable for viscosity experiments. In conclusion, the use of teepol as an alternative material in viscosity experiments offers an innovative solution to the visual challenges faced when using oil.